Yield and quality of root fruits of sugar beet when grown in crop rotation with short rotation - Hanhur, V.; Filonenko, V. (Scientific Progress & Innovations, 2023)
Sugar beet (Beta vulgaris L.) is the second largest sugar crop in the world after Sugarcane. Sugar beet is not only a source of material for sugar production, but also an important by-products of its conversion, including pulp and molasses, which are widely used in animal feed rations. Sugar beet is a very demanding crop for its predecessors. A number of scientists noted that not only the predecessors but also the crops that precede them have a significant effect on the formation of root crop yields. In the studies conducted during 2016‒2022 at the Poltava State Agricultural Experimental Station named M. Vavylov, was found that the highest yield of sugar beet root was obtained in a 5-field crop rotation, where sugar beet was cultivated after spring barley in a link with perennial legumes of two-year use (alfalfa) ‒ 42.1 t/ha. The yield of sugar beet, when it cultivated in a crop rotation after winter wheat, the predecessor of which was peas for grain, black steam, sainfoin for one cut, alfalfa for two years for green fodder, was 40.4‒41.7 t/ha, or lower compared to sowing after spring barley by 0.4‒1.7 t/ha or only 1‒4 %. It should be noted that according to the results of the analysis of variance, such a decrease in the yield of root crops is not significant and is within the limits of the NIR (3.46 t/ha). The results of the study indicate that the sugar content of sugar beet roots in the crop rotation, where winter wheat was sown after peas for grain, was higher by 0.7 % (absolute) than in the crop rotation with black steam (19.0 and 18.3 %, respectively). In our opinion, the decrease in sugar content of root vegetables in grain-steam crop rotation, compared to grain crop rotation, under the same fertilizer system, is due to an abundance of nitrogen nutrition. Thus, the results of the study showed that in crop rotations with short rotation term, an equivalent predecessor for sugar beet is winter wheat, the predecessor of which was black steam, after peas for grain, sainfoin for one cut, two-year alfalfa for green fodder and spring barley, that was preceded by two-year alfalfa for green fodder.